Fly Guy and the alienzz - Arnold, Tedd (New York : Cartwheel Books, 2018)
Buzz is filming a movie about aliens from Outer Space, who capture Fly Guy and Buzz Boy--and our two heroes must outsmart the aliens, with some help from Dragon Dude and Fly Girl.
2.4
K-3
530L
Keywords: Flies -- Fiction; Extraterrestrial beings -- Fiction; Motion pictures -- Production and direction -- Fiction; Imagination -- Fiction